Perancangan Aplikasi E-Commerce Menggunakan Cloud Computing dan Arsitektur Severless Lambda - Liem Margareth Santoso; Frederik Samuel Papilaya (Universitas Methodist Indonesia, 2024)
E-commerce applications are one area that continues to develop rapidly in the digital industry. The use of cloud computing and serverless lambda technology has provided many advantages in developing and managing e-commerce applications. However, the need for flexibility, scalability, and operational efficiency is increasingly driving the adoption of serverless architecture as an approach to building adaptive and cost-effective e-commerce applications. The app allows sellers to market products, take orders, and manage inventory efficiently, while customers can easily browse the product catalog, add items to their shopping cart, and complete checkout. Through performance analysis and evaluation, we show that the serverless Lambda architecture is capable of automatically providing scalability according to application traffic requirements. Additionally, a serverless approach also reduces the burden of infrastructure administration, allowing developers to focus on developing features and functionality that have a direct impact on the user experience.